1987
DOI: 10.1210/jcem-65-6-1177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hypothalamic Dysfunction in Growth Hormone (GH)-Deficient Patients Using SingleVersusMultiple Doses of GH-Releasing Hormone (GHRH-44) and Evidence for Diurnal Variation in Somatotroph Responsiveness to GHRH in GH-Deficient Patients*

Abstract: To examine the efficacy of multiple doses of GHRH-44 to enhance GH secretion and to determine the number of GHRH-44 doses required to exclude hypothalamic dysfunction, 12 doses of GHRH-44 were administered iv every 2 h to 4 GH-deficient patients beginning in the morning (group A) and to 4 GH-deficient patients beginning in the evening (group B). Five additional GH-deficient patients (group C) were given 4-18 GHRH-44 doses. The first and last doses were 5 micrograms/kg; all others were 1 microgram/kg. Higher GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…Both baseline and pulse amplitudes were higher at night than during the day in our patients, a phenomenon that clearly cannot be attributed to GHRH. This is in agreement with other, more circumstantial evidence that enhanced nocturnal GH secretion is not fully attributable to GHRH (36,48,62,69) and supports the concept that decreased somatostatin tone contributes to enhanced nocturnal GH secretion (70). In the absence of GHRH action, it is either somatostatin withdrawal, ghrelin pulses, or another, unknown oscillator that must be responsible for residual nocturnal pulse generation.…”
Section: Discussionsupporting
confidence: 91%
“…Both baseline and pulse amplitudes were higher at night than during the day in our patients, a phenomenon that clearly cannot be attributed to GHRH. This is in agreement with other, more circumstantial evidence that enhanced nocturnal GH secretion is not fully attributable to GHRH (36,48,62,69) and supports the concept that decreased somatostatin tone contributes to enhanced nocturnal GH secretion (70). In the absence of GHRH action, it is either somatostatin withdrawal, ghrelin pulses, or another, unknown oscillator that must be responsible for residual nocturnal pulse generation.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in the rat (15) and man (7,8) have shown that the response to bolus GHRH stimulation is greatest at times of endogenous GH secretion (when SRIF tone is low and stored GH is available for release), and lowest during the refractory phase between pulses (when SRIF tone is high and stored GH pools are depleted). Knowledge of the pre-stimulatory secretory state is therefore important for interpreting results, and, although many studies have shown a reduced GH response to GHRH stimulation in children with severe idiopathic GH deficiency (16)(17)(18), the variability in this test has limited its usefulness in differentiating children with less marked GH insufficiency from short normal controls (19).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to differentiate the hypothalamic from the pituitary form of GH deficiency with the growth-hormone-releasing hormone (GHRH) test has been doubted [1,2,6,7,15,16], but on the basis of studies performed in small and not homogeneous groups of growth-hormone (GH)-deficient children.…”
Section: Introductionmentioning
confidence: 99%